Amateurism and professionalism in work and learning. Issue 6 (19th August 2014) - Edwards, Richard
Abstract : Purpose: This article explores the concept of amateurism as a form of critique and addition to the concepts of professionalism, professional work and education. Design/methodology/approach: This is theoretically driven article based upon a review of the historical and sociological literature on amateur-professional relations in various work contexts. Findings: While amateurism is usually conceived pejoratively, the notion of doing something 'for the love of it', even if one is not formally qualified, opens up the possibilities for conceiving new forms of work, worker and sets of working relationships based upon different conceptions of expertise. Drawing upon historical and contemporary studies of the contribution of amateurism to professional work, and exploring the role of digital technologies in enabling amateurs to contribute to forms of professional practice, the article explores some of the challenges posed for work and learning, and suggests some lines of research to be explored. Originality/value: There has been little to no consideration of amateurism as a positive contribution to considerations of professional work, nor exploration of the expertise and learning of amateurs.